ADAPTING MIDDLE EASTERN ISLAMIC CULTURE: A JOURNEY OF WESTERN MUSLIM WOMAN IN G. WILLOW WILSON’S THE BUTTERFLY MOSQUE - Ramadhina Ulfa Nuristama; Nestiani Hutami; Inka Zahwa Sabrina; Anas Armasta (Universitas Gadjah Mada, 2022)
The 9/11 tragedy in America has created more intense tension between America and Middle Eastern cultures. Then, the term Islamophobia emerged, where many non-Muslims feared Islam. Even until now, they associate Islam with terrorism. However, this situation led Willow, the main character, to decide to study and convert to Islam. Although not the main point that caused Willow to convert to Islam, the decision was made after the 9/11 tragedy. Willow represents a western woman who intentionally learns Islamic teachings. This study will use a qualitative descriptive method to explore events and cultures surrounding the main character. Therefore, there are two purposes of this study. The first is to delve into how the culture of Middle Eastern Muslim women is portrayed. Secondly, is to examine how the main character adapts to the culture of Middle Eastern Muslim women. In analyzing the data, this study applies postcolonial feminism theory to understand the cultural differences between Middle Eastern and Western Muslims, particularly regarding women. This study shows that the main character faces cultural challenges different from her origin country in carrying out religious practices, especially Islam. Nonetheless, the main character can adapt to the values of both cultures.